The Threshold Grace: Meditations in the Psalms - Ainsworth, Percy C. (Percy Clough), 1873-1909 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Threshold Grace: Meditations in the Psalms" by Percy C. Ainsworth is a devotional book consisting of reflections on various Psalms written during the early 20th century. This collection seeks to explore the themes of faith, trust, and the divine relationship between humanity and God. Ainsworth, known for his spiritual writings, aims to guide readers in understanding the significance of their faith in the context of daily life and challenges. The book presents a series of meditations that delve into the complexity of human experiences, inviting readers to reflect on their spiritual journeys. Each meditation focuses on a specific Psalm, offering insights about trust in God, the importance of prayer, and the challenge of dealing with life's trials. Ainsworth emphasizes that faith is not merely a temporary feeling but a continuous attitude that guides response to life's uncertainties. Through themes of sorrow, joy, petition, and communion with God, the author encourages a deeper understanding of spiritual resilience, suggesting that true peace and purpose are found in an abiding relationship with the divine. This collection serves as a spiritual companion for those seeking solace and strength through the wisdom of the Psalms. (This is an automatically generated summary.)
Release date is 2004-08-24
Produced by David Newman, Clare Boothby and PG Distributed Proofreaders
Keywords: Bible. Psalms -- Meditations